2005
DOI: 10.1002/pon.979
|View full text |Cite
|
Sign up to set email alerts
|

The enhancing connections program: pilot study of a cognitive‐behavioral intervention for mothers and children affected by breast cancer

Abstract: In 2005, approximately 211,240 women in the US will be diagnosed with early stage breast cancer and an estimated 22% will be child rearing. Research reveals that both mothers and children have elevated distress attributed to the cancer; struggle with how to talk about and deal with the impact of the cancer; and both fear the mother will die. The Enhancing Connections Program (EC) was developed to reduce this cancer-related distress and morbidity. The program involves five, 1-hour educational counseling session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 39 publications
7
79
0
Order By: Relevance
“…Parents are aware of this fact, as results from a recent study show that the second most commonly identified practical problem for cancer patients is child care (45%), right after finances (48%), whereas the most commonly identified familial problem is dealing with children (87%) (Shim, Shin, Jeon, & Hahm, 2008). Indeed, parental cancer has been associated with less parental availability, or even with some parental disengagement, which can hinder adolescents' development and adaptation (Folkner & Davey, 2002;Lewis et al, 2006). Parents are responsible for identifying and responding to their children's needs, but coping with cancer and the intensity of associated treatments necessitates such demanding and numerous adjustments that parents may not always be able adequately fulfill this role (Lewis et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Parents are aware of this fact, as results from a recent study show that the second most commonly identified practical problem for cancer patients is child care (45%), right after finances (48%), whereas the most commonly identified familial problem is dealing with children (87%) (Shim, Shin, Jeon, & Hahm, 2008). Indeed, parental cancer has been associated with less parental availability, or even with some parental disengagement, which can hinder adolescents' development and adaptation (Folkner & Davey, 2002;Lewis et al, 2006). Parents are responsible for identifying and responding to their children's needs, but coping with cancer and the intensity of associated treatments necessitates such demanding and numerous adjustments that parents may not always be able adequately fulfill this role (Lewis et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, cancer incidence is rising among young adults, particularly among women age 20 to 39 (Canadian Cancer Society's Steering Committee, 2009). Recently, it has been estimated that 22% of women affected by breast cancer have children at home (Lewis, Casey, Brandt, Shands, & Zahlis, 2006). Thus, an important number of children and adolescents are likely to experience serious familial disruptions when one of their parents is suffering from cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The YSR and TRF are parallel versions of the original CBCL instrument designed to measure the same variables by each type of informant; for brevity's sake they will all be referred to here as 'CBCL measures'. Following previous studies (Visser et al, 2005;Lewis et al, 2005), Internalising, Externalising and Total Problem scores will be examined here as indices of child problems. For ethical reasons, six items about bowel and sexual problems were omitted from the CBCL.…”
Section: Child Emotional and Behavioural Problemsmentioning
confidence: 99%
“…A lot of studies indicate that family functioning is more predictive for children's psychological adjustment than any disease-related parameter, such as duration, prognosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%